Kesalahan Fonetik pada Pidato Berbahasa Arab Mahasiswa Jurusan Pendidikan Bahasa Arab UIN Antasari Banjarmasin - Almajudha, Yahana; Muradi, Ahmad; Munadi, Fathullah; Abdullah, Mohamad (UIN ANTASARI, 2024)
Arabic speech is one of the lessons learned by the fourth-semester students in Arabic Language Education Department at Antasari State Islamic University Banjarmasin which is included in the khiṭābah wā masrahiyyah course. In speech activities, pronunciation errors or phonetic errors require more attention because these errors will affect the meaning captured by the listener. The purpose of this study was to find the phonetic errors in Arabic speech of Arabic Language Education students of Antasari Islamic State University. This research utilized a qualitative research using content analysis. The data collection techniques used were documentation, free listening, and note-taking techniques. Then the data were analyzed using error analysis techniques. From the data collected, it can be concluded that the phonetic errors in Arabic speech were by subsituting letters with other letters, resulting in a total of 13 forms of sound changes. All forms of letter substitution occur on letters that are suspected of having similar sounds in Arabic.